The effect of misinformation acceptance on COVID-19 prevention behaviors - Leila Dehghani; Tahereh Tamimi; Mazyar Ganjoor; Parisa Eskandari (International Journal of Information Science and Management)
The acceptance of misinformation about COVID-19 has had irreversible consequences on public health during the pandemic. The current study was conducted to investigate the effect of misinformation acceptance on preventive behaviors related to COVID-19 and to help health policymakers prioritize the fight against the epidemic. This cross-sectional survey was conducted on 626 Iranians over 15 years old using the available sampling method (March 4–2022 to May 14–2022). The data were analyzed in SPSS-19. With the status of vaccination with acceptance of misinformation, the evidence of higher acceptance of misinformation is seen in people who received a lower dose or did not receive the vaccine. Weaker economic groups have been more exposed to misinformation and accepting it. A negative correlation was found between preventive behaviors and acceptance of misinformation. Therefore, the higher the acceptance of misinformation, the participants observed the weaker preventive behaviors and the acceptance of misinformation along with age and the moderating effect of basic knowledge about COVID-19 predict preventive behavior in misinformation acceptance. The present study has a valuable contribution to our understanding of the effect of acceptance of misinformation on preventive behaviors and the characteristics of acceptance of misinformation as an essential predictor of preventive behaviors. Hence, identifying misinformation and preparing protocols for health advisors to provide people with correct information have a high value in the containment of the pandemic.